Effect of Combined Hydroxyurea and Chelation Therapy in Reducing Serum Ferritin Level, Liver and Spleen Size in Transfusion Dependent Thalassaemia Major Patients. - Tatheer Zahra, Wajeeha Amber , Itrat Fatima , Tatheer Zahra, Wajeeha Amber , Itrat Fatima (Journal of Rawalpindi Medical College, 2019)
Background: To compare hydroxyurea plus iron chelation therapy with iron chelation therapy alone in controlling iron overload in children with beta thalassaemia major. Methods: In this comparative study forty thalassaemia major, cases undergoing routine blood transfusion, were observed in iron chelation plus hydroxyurea group (n=20) and iron chelation therapy alone (n=20). The study outcome was measured in terms of impact of continuous blood transfusions on the size of liver ,spleen and Serum. Ferritin levels when compared among those given iron chelation therapy with hydroxyurea and those given iron chelation alone. Results: Mean age of patients was comparable among the two groups. Overall, males were slightly greater in proportion than females (52.5% versus 47.5%). The mean liver size, spleen size and ferritin levels were significantly low in hydroxyurea group compared to no hydroxyurea group (p-value, <0.001). Conclusion: Hydroxyurea plus iron chelation therapy is better than iron chelation therapy alone in controlling iron overload in terms of enlargement of liver, and also limiting iron stores.